Lelang Jabatan dalam Sistem Hukum di Indonesia - Sari, Elidar (Jurnal Ilmu Hukum Reusam, 2015)
The case of official positional auction under Indonesia legal system is not yet determined hence on this case, the civil servant regulation is adopted as a reference on goverment organization. Therefore, the government body or state officials may consider any policy in order to fullfil the public demand. Indonesian officials have right to act based on Fress Ermessen’s principle which can provides the freedom for authorized party to make decision as long as it is still on the track and does not overreach legal procedure. Consequently, the official positional auction is considered as a policy that belong to all state officials as long as it does not againts the law.